Analysis of the Role of Stakeholders in the Governance of Street Vendors in Metro City - Theresia Helen Simarmata; Dedy Hermawan; Intan Fitri Meutia; Bambang Utoyo (Eastasouth Institute, 2026)
Street vendor governance in developing countries presents complex challenges between protecting economic rights and maintaining public order. This study aims to analyze stakeholder roles, relationships, and interactions in street vendor governance in Metro City, and identify supporting and inhibiting factors affecting policy implementation effectiveness. Using a descriptive-exploratory qualitative approach, data were collected through semi-structured interviews with nine informants including government agencies, vendor associations, and media, complemented by observation and documentation. Results indicate that governance involves three systematic stages: planning, implementation, and evaluation with collaborative participation from the Trade Office, Civil Service Police Unit, Public Works Office, Transportation Office, Cooperatives and SMEs Office, and vendor associations based on Regional Regulation Number 09 of 2017. Supporting factors include comprehensive regulation, cross-sector coordination, government-association synergy, and program innovations such as Kue Ping and MAPAN Store. However, governance effectiveness is hindered by inadequate infrastructure at relocation sites, vendor resistance, low legal awareness, weak public trust, and limited human resources and budget. The study recommends infrastructure improvement, enhanced communication transparency, continuous education programs, dedicated budget allocation, digitalization of monitoring systems, and balanced enforcement mechanisms to achieve sustainable street vendor governance.